Information in advertising industry to fulfill consumers business information needs / Mohd Sazili Shahibi, Mardzuki Mazlan , Khairul Mizan Taib... [et.al]. - Shahibi, Mohd Sazili Shahibi; Mazlan, Mardzuki Mazlan; Taib, Khairul Mizan; Zaini, Muhamad Khairulnizam Zaini; Ali, Juwahir Ali; Taib, Khairul Mizan Taib (2011)
Advertising is an industry that contributes in the economic growth of a country. Advertising involved pouring information to the public and audience by an advertiser and firm on the products and services provided by them. This can be done by using several media that are available, which are printed media, electronic media, and Direct mail, Outdoor, Transit and Supplementary Media that are crucial to disseminating the information. The selection of media is important because it will be measured in order to determine the effectiveness of an advertising campaign. Advertising creates a parameter where firms compete in a free market economy which will motivate them to be more innovative and creative thus it will bring a lot of benefits to the economy. The issues of advertising industry must be discussed to enable public to know the importance of advertising industry. Objective of this study is to examine people awareness and perception on advertising as sources of information in order to fulfill their business information needs as a consumer in the market. This study will be initiated by reviewing literatures on the use of information in advertising industry that used to disseminate information as well as to present adequate information in an ethical manner. By doing so, it does not compromise the accuracy of the information as well as to create innovation on creating effective advertisements in every channel. A study has also been undertaken through questionnaires survey among managers, marketing staff, designers and public respondents. Findings show that somehow most of the respondents are still lack of understanding in the use of information in advertising industry and how to use it without breaching the intellectual property. The study indicated that most of the respondents have low knowledge in advertising information. However, they agreed with advertising and information has a strong connection and advertising information is a powerful tool of information sources in providing reliable data. Most of the people depend mostly on advertising and media to find their needed information. They need information to perform tasks, making decisions and perform actions. It is time consuming when crucial information is not there to be used or not updated to comply with fast changing situations in modern Information Technology era. Majority of the respondents (63%) agreed that advertising provide needed information, 6% totally agreed and 31% disagreed with the statement. Findings show that information content of advertising may influence how people think about certain product or service. The overall results demonstrated that the respondents rely quite significantly on advertising to obtain information on products and services. Keywords: Advertising; Information; Advertisement; Economy; Consumer